OBTAINING NITROGEN AND SULFUR CONTAINING OLIGOMERS AND STUDYING PHYSICAL-CHEMICAL PROPERTIES - Berdiyev, Sanjar (Innovatsion texnologiyalar, 2024)
The optimal proportions of organic additives containing nitrogen and sulphur, their structure were studied in the article by IR-spectroscopy analysis, and their physico-chemical properties were studied. According to the obtained preliminary results, it was found that the proposed NS-1 brand additives are resistant to mechanical wear formed on the metal surface under the influence of fuels.